Coacervates as Prebiotic Reactors - Kolb, Vera (Proceedings of the Wisconsin Space Conference, 2014)
In this work we summarize the important findings about coacervates as prebiotic reactors. We have found out that it is possible to run a chemical reaction in a coacervate, which fulfills the early predictions by Oparin that coacervates may have been the original prebiotic reactors. We have prepared two types of coacervates and have found that Passerini reaction in water occurs in both of them.Â 